Trend Analysis of Broiler Chicken Egg Prices in Bengkulu City - Reflis Reflis; Sindi Anggeriyanti; Basuki Sigit Priyono (Journal of Global Sustainable Agriculture, 2021)
Chicken eggs are one of the most common eggs produced by breeders in Bengkulu. The price of purebred chicken eggs is very affordable compared to other types of eggs. The demand for purebred eggs will continue to grow along with the increase in population. This research aims to determine the pattern of price development of broiler chicken eggs in Bengkulu City and the trend of broiler egg prices in Bengkulu City. This research uses Trend Analysis with a simple linear regression method. An estimate made or forecast in the future with statistical analysis methods. It requires a wide variety of data (information) that is quite a lot and visible in a significant enough time to make a measuring instrument so that every component that affects the development to how much change occurs can be seen using this research. The information used was obtained from the Central Bureau of Statistics of Bengkulu City. The result obtained is a positive trend where the line of price development depicted increases continuously. The trend that continues to increase is influenced by several things that occur within a year, including Eid al-Adha, Christmas, and the new year. The linear trend line is Y = 1942,9 + 3,96 X + E where R^2 = 0,5661